Kajian Pengaruh Bobot Kokon Induk Terhadap Kualitas Telur Persilangan Ulat Sutera (Bombyx mori L.) Ras Jepang Dengan Ras Cina - Y. C. Endrawati; H. C. H. Siregar; M. Kaomini (Universitas Andalas, 2006)
Uniformity of cocoon weight is one important factor of parent stock in order to get a good quality of crosses. In consequence, some cocoons that too heavy or light become wastes even come from a good strain. The research that conducted at Forest and Nature Conservation Research and Development Center, Bogor, had an objective to know the effect of parent cocoon weight on the egg and larval quality among four reciprocal crosses. Strain 803 (Japanece race) and strain 804 (Chinese race) with different cocoon weight were used as parent stocks. The effect of cocoon weight was evaluated on the economical traits including number of eggs, weight of eggs, hatchability, weight of newly hatched larvae and hatching period through crossing method, wherein parents, F1s and reciprocals were involved. The result showed that number and weight of eggs were significantly different. Maximum number of eggs and maximum weight of eggs were 650 and 0.61 mg, respectively, that belongs to (803B x 804B), heavy cocoon of 803 female crossed with heavy cocoon of 804 male. Strain 803 female influenced those characters. Types of crossing had not an effect on hatchability, weight of newly hatched larvae and hatching period.